ORGANIZATIONAL CULTURE ON IMPLEMENTATION OF PROFESSIONAL TRANSFER PROGRAM AT PT JASA MARGA (PERSERO) TBK. - Umi Rusilowati; Agus Budiyana (SAMPURASUN, 2021)
The impact of technological developments and the application of GNNT or Cashless in toll road transactions can trigger company to terminate employment, but the company is not allowed to lay off, this is a challenge for Jasa Marga so that there are no layoffs and operational services in the field continue to run by Government policies and the PUPR Ministerial Decree. In 2017-2019 PT Jasa Marga (Persero) Tbk. made a change by preparing a voluntary Professional Transfer Program (A-Life) for employees. In this process, Jasa Marga Management, the Employees, and Employees Union are committed to jointly leading the change management process in a professional transfer program that takes into account the interests of the Company and the Employees, however should improve the quality of organizational culture as well. The method used a qualitative approach based on a case study to examine the state of natural objects, in which the researcher is the key tool, the data collection technique is performed by triangulation (a combination of observations, interviews, documents), the resulting data tends to be qualitative data, analytical data is inductive/qualitative and research finding of qualitative research is about understanding meaning, understanding unique, construct phenomena and find hypotheses. The conclusion there were the process, obstacles, and effectiveness of change management implementation in the professional transition program (ALife) and organizational culture which has not been implemented optimally.